The Influence of Quasi- or Hybrid-Authority Governments in Promoting the Emergence of a Sequential Decentralization Model: A Comparison of the United Kingdom and France Model - Anajeng Esri Edhi Mahanani; Pujiyono Suwadi; Jadmiko Anom Husodo (UIN Sunan Kalijaga Yogyakarta, 2026)
Structural inconsistencies regarding the legal status of the Nusantara Capital City Authority (IKN) and its Head who simultaneously act as special regional government administrators and central government representatives have produced a governance setup marked by dual authority. This institutional overlap is exacerbated by the fact that the IKN Authority and its leadership also operate as contracting parties in private investment agreements for capital development. Such regulatory design under the IKN Law departs sharply from constitutional and statutory provisions that traditionally govern regional administration. Addressing these discrepancies, this article applied a normative legal research design with a comparative approach. The analysis demonstrates that a quasi- or hybrid-authority governance model provides a novel theoretical framework to map the relational dynamics between the IKN Authority and the Central Government. To eliminate statutory disparities while respecting constitutional local governance principles, the paper argues for a sequential asymmetric decentralization model adapted from Tulia G. Falleti’s theory—an approach previously implemented in jurisdictions such as the United Kingdom and France. Beyond theoretical contributions, these findings offer concrete guidance for future policy planning and regulatory design for the national capital within Indonesia's regional autonomy framework Ketimpangan pengaturan kedudukan Lembaga dan Kepala Otorita Ibu Kota Nusantara (IKN) sebagai penyelenggara Pemerintahan Daerah Khusus Ibu Kota dan juga sebagai wakil pemerintah pusat, memunculkan model pemerintahan dengan kewenangan yang ganda. Problematika semakin menguat melihat Lembaga dan Kepala Otorita Ibu Kota Nusantara juga bertindak sebagai pihak dalam perjanjian investasi pembangunan IKN. Pengaturan UU IKN juga memiliki perbedaan mendasar dengan pengaturan pemerintahan daerah pada konstitusi dan undang-undang pemerintahan daerah. Untuk dapat mengurai permasalahan ketimpangan tersebut, penulisan jurnal ini menggunakan metode penelitian normative dengan studi perbandingan. Ditemukan hasil bahwa model quasi atau hybrid authority government merupakan model baru yang dapat digunakan untuk menggambarkan pola hubungan kewenangan Lembaga Otorita Ibu Kota Nusantara dengan Pemerintah Pusat. Agar tidak ada ketimpangan pengaturan kedudukan Lembaga Otorita IKN dengan segala kewenangan yang dimiliki dan melihat ketentuan konsep pemerintahan daerah sebagaimana diatur dalam konstitusi dan undang-undang, maka perlu diselenggarakan model desentralisasi asimetris sekuensial yang lahir dari adopsi teori sequential decentralization milik Tulia G. Falleti, yang juga diterapkan di beberapa negara, misal Inggris dan Perancis. Artikel ini diharapkan dapat memberikan sumbangsih model pengaturan penyelenggaraan desentralisasi asimetris di Ibu Kota Negara pada masa depan. Temuan model ini merupakan temuan baru yang dapat menjadi pertimbangan rancangan kebijakan penataan Ibu Kota Negara dalam rezim otonomi daerah.